2022
DOI: 10.55197/qjssh.v3i6.192
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction in Matabungkay Beach Hotel, Batangas: Online Reviews From Selected Travel Sites

Abstract: As tourism industry progress the sectors under it smartly intertwined to come up with a new and innovated form in which one of its results has been evidently making a mark to the market this particularly refers to the “beach hotel”. In line with this, this progressive state happening at present leads us to a more convenient form of knowing the status of the place through an accessible online travel websites basically navigates travellers to accurately identify the information and actual reviews of other guests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…(2017), tangibility entails that the quality of hotel services is seen through tangible proofs utilized by the hotels for example, facilities and equipment, technology together with customer-facing visual resources. In addition, this finding is consistent with the study findings of Yebron et al (2022) and Go et al (2022) where tangibility was the highest assessed dimension which signifies that guests are more concerned with the objects that can be seen and touched. Similarly, the most important criterion for an authentic restaurant is an excellent physical facility, which includes the restaurant's location, temperature, interior designs, and overall ambiance of its environment (Sanchez, 2021).…”
Section: Resultssupporting
confidence: 91%
“…(2017), tangibility entails that the quality of hotel services is seen through tangible proofs utilized by the hotels for example, facilities and equipment, technology together with customer-facing visual resources. In addition, this finding is consistent with the study findings of Yebron et al (2022) and Go et al (2022) where tangibility was the highest assessed dimension which signifies that guests are more concerned with the objects that can be seen and touched. Similarly, the most important criterion for an authentic restaurant is an excellent physical facility, which includes the restaurant's location, temperature, interior designs, and overall ambiance of its environment (Sanchez, 2021).…”
Section: Resultssupporting
confidence: 91%
“…In comparison, the lowest weighted mean obtained was AAM Transient House, with an overall mean of 6.28, respectively. With that, the apartment hotels need to consider their customer satisfaction and customer reviews because the purpose of specifying the feedback from the actual experiences of the guests is to determine the service if it needs improvement in terms of the quality of the service that could push it through with more profitable and delighted customers (Yebron et al, 2022). Aside from that, excellent customer satisfaction and review aim to improve the company's quality control since it provides valuable insights into the strengths and weaknesses of the hotel's guest experience, facilities, and overall services.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of analyzing guest feedback is to identify whether the quality of service requires enhancements to increase customer satisfaction and profitability (Yebron et al, 2022). This research has primarily analyzed reviews and found more negative than positive responses for selected apartment hotels in Metro Manila listed on Agoda.…”
Section: Introductionmentioning
confidence: 99%